Group Delegated ID-Based Proxy Reencryption for the Enterprise IoT-Cloud Storage Environment. (15th June 2021) - Kim, Won-Bin; Seo, Daehee; Kim, Donghyun; Lee, Im-Yeong
Abstract : In general, ID-based proxy reencryption (IBPRE) includes data transfer in a 1 : 1 manner between a sender and receiver. Therefore, only the data owner has the authority to decrypt or reencrypt the data that is encrypted with his/her public key. However, in an environment with data self-sovereignty, such as an enterprise IoT-cloud environment, the data are directly managed by cloud once data is uploaded from user-controlled IoT devices. In such a situation, there is no way of sharing data if the data owner has no access over the data due to being outside the workplace and other issues. In this study, to solve this problem, data can be shared even when the data cannot be accessed by delegating the authority of the data owner to generate the reencryption key to other users. In addition, by solving the security threats that may appear in this process, data sharing can be performed securely and efficiently in the corporate environment.